2014
DOI: 10.11606/issn.1806-6976.v10i2p85-92
|View full text |Cite
|
Sign up to set email alerts
|

Concepção de profissionais de saúde que atuam em emergência de saúde mental

Abstract: O presente estudo comparou as concepções sobre doença mental de profissionais administrativos, de enfermagem e médicos dos serviços de saúde de urgência no município de Londrina-PR. O delineamento foi transversal, utilizando a escala OpinionsAbout Mental Illness (OMI) com uma amostra aleatória de 30% dos profissionais, totalizando 96 sujeitos no período de 2010 a 2011. Os dados foram submetidos à análise estatística pelo StatisticalPackage for Social Sciences (SPSS). Para dois fatores da escala ODM e com os en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
1
3
0
7
Order By: Relevance
“…A study with emergency services professionals has shown similar results, found in the attitudinal profile characteristics of this population as little conscious of the factors that trigger mental illness (11) , even if they are not specific services of the psychosocial care network. Substitutive services, under the psychosocial rehabilitation proposal, seek to define a new social place for the treatment and rehabilitation of people with mental suffering, promoting actions aimed at the process of social integration (20) .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…A study with emergency services professionals has shown similar results, found in the attitudinal profile characteristics of this population as little conscious of the factors that trigger mental illness (11) , even if they are not specific services of the psychosocial care network. Substitutive services, under the psychosocial rehabilitation proposal, seek to define a new social place for the treatment and rehabilitation of people with mental suffering, promoting actions aimed at the process of social integration (20) .…”
Section: Discussionsupporting
confidence: 63%
“…In addition, it was found that nursing professionals, when compared to professionals of services specifically aimed at mental health, presented a more stereotyped view of these patients. This result would refer to the small contact these professionals have with these users (11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudo comparativo entre países europeus, (12) incluindo Portugal, faz uma aproximação com a temática atitude, porém não evidencia especificamente a realidade das atitudes de enfermeiros de cuidados primários. No Brasil, inexistem estudos com enfermeiros de cuidados primários frente à doença mental, e os que se aproximam foram realizados com enfermeiros de unidades psiquiátricas e de urgência/emergência geral, (13,14) com uso da escala ODM. Assim, pouco se sabe nos dois países sobre as Resumen Objetivo: Analizar comparativamente las actitudes y experiencias de enfermeros de atención primaria de Brasil y Portugal con relación a personas con enfermedad mental.…”
Section: Introductionunclassified